PECULIARITIES OF ASSESSING PATHOMORPHOLOGICAL CHANGES IN INFLAMMATORY UROLOGICAL DISEASES - Shadmanov Jakhongir Alisherovich (The Conference Hub, 2025)
In recent years, general terms such as lower urinary tract symptoms and overactive bladder have been adopted by urologists around the world. The emergence of these terms has standardized attention to urological diseases, bringing them to a general consensus on their terminology. Urological diseases have become global in the world and in Uzbekistan. This is due to the deterioration of the climatological and geographical conditions in most parts of the world, including the regions around the Aral Sea.